Web and Wireless Geographical Information Systems 11th International Symposium, W2GIS 2012, Naples, Italy, April 12-13, 2012, Proceedings - Di Martino, Sergio; Peron, Adriano; Tezuka, Taro (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2012)
This book constitutes the proceedings of thw 11th International Symposium on Web and Wireless Geographical Information Systems, W2GIS 2012, held in Naples, Italy, in April 2012. The 13 full and 4 short papers presented in this book were carefully reviewed and selected from 32 submissions. The papers are organized in topical sections names: 3D and multimodal spatial interaction; positioning; spatial human-computer interaction; trajectory analysis; geo semantics; and sensor networks.